Improving electrochemical performance of Nano-Si/N-doped carbon through tunning the microstructure from two dimensions to three dimensions. (1st February 2020) - Fan, Peng; Lou, Shuaifeng; Sun, Baoyu; Wu, Libin; Qian, Zhengyi; Mu, Tiansheng; Ma, Yulin; Cheng, Xinqun; Gao, Yunzhi; Zuo, Pengjian; Du, Chunyu; Yin, Geping
Abstract: Silicon-based anode for lithium-ion batteries (LIBs) has attracted much attention due to its high theoretical capacity, low operating potential and abundant resources. However, the large volume expansion/shrink during the lithiation/delithiation process induces extreme damage to the electrode microstructure. The resulting failure of electrical contact between silicon and current collector will severely deteriorate the cycling stability. Herein, a three-dimensional nano-Si/N-doped carbon network was obtained by a facile approach with NaCl templates. The N-doped carbon network not only significantly improves the electronic conductivity, but also ensures a valid electrode microstructure through a highly elastic carbon framework. Additionally, a two-dimensional nano-Si/N-doped carbon sheet was prepared without NaCl templates, revealing the boosting action of NaCl templates in the microstructure adjustment from low dimension to spatial crosslinking. The optimal three-dimensional nano-Si/N-doped carbon composite can deliver a high specific capacity of 1396 mAh g −1 with a capacity retention of 84.3% after 100 cycles at 200 mA g −1 . This study provides effective guidance for novel Si-based anode design to achieve high-energy LIBs with excellent cycling stability. Graphical abstract: Image 1